Pengaruh Massage Punggung Terhadap Peningkatan Kualitas Tidur Lanjut Usia - Maryaningsih Maryaningsih; Sulaiman Sulaiman; Anggriani Anggriani; Wahyu Wijanarko; Fajrillah Fajrillah (Jurnal Kesehatan dan Fisioterapi, 2021)
Back massage is a touch of the hand that is done by means of stroking, petrisage, friction and skin rolling movements with the aim of improving the sleep quality of the elderly, because this therapy has the ability to produce a relaxation response that makes the body relax and feel comfortable when entering a rest or sleeping time. The purpose of this study was to determine the quality of sleep of the elderly at the Taman Bodhi Asri Binjai Panti. This research method uses a quasi experiment. The population in this study were 86 elderly people with poor sleep quality who were in the Taman Bodhi Asri Binjai Panti. The number of samples taken by the researcher was 46 respondents using the simple random sampling technique. The results of the Wilcoxon rank test analysis on the pretest and posttest obtained a Z value of -3.522, and Assimp. Signed 0.002 or (p <0.05. There is a significant effect of back massage on the quality of sleep of the elderly at the Taman Bodhi Asri BinjaiKeyword: sleep, quality, elderly, back, massage